Zat gizi, massa lemak tubuh, dan tekanan darah pada wanita vegetarian dan nonvegetarian berusia 20-30 tahun - Kirana, Stela Maris Adinda Budi; Murbawani, Etisa Adi; Panunggal, Binar (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background : Vegetarians tend to have a risk of underfat. Several studies have reported that vegetarians have lower fat and higher fiber intake, lower body fat mass and blood pressure than nonvegetarians. There are only few studies about those variabels in 20-30 year-old subject. Objective : To analyze the difference of nutrients intake, body fat mass, and blood pressure between 20-30-year-old vegetarian and nonvegetarian women.Methods : Cross-sectional study design in 26 vegetarian women and 26 nonvegetarian women who was selected by consecutive sampling. Nutrients intake were obtained by Semi Quantitative Food Frequency Questionaire (SQFFQ) and analyzed by Nutrisurvey. Body fat mass was measured using Bioelectrical Impedance Analysis (BIA). Blood pressure was measured using Mercury sphygmomanometer. Data were analyzed using Independent t-test and Mann-Whitney test.Result : There were 38.5% of vegetarians and 3.8% of nonvegetarians classified as underfat. There were 30.7% of vegetarians and 50% of nonvegetarians classified as prehypertension. There were difference in fat (p=0.005), saturated fatty acid (p=0.000), monounsaturated fatty acids (p=0.002), polyunsaturated fatty acids (p=0.043), fiber (p=0.000), potassium (p=0.000), magnesium (p=0.004); body fat mass (p=0.021); and sistolic blood pressure (p=0.004) between both of groups. There weren’t difference energy intake (p=0.098), carbohydrate (p=0.207), protein (p=0.535), sodium (p=0.784), calcium (p=0.798), and diastolic blood pressure (p=0.799) between both of groups.Conclusion : Between vegetarian group and nonvegetarian group, there were difference in fat, saturated fatty acid, monounsaturated fatty acids, polyunsaturated fatty acids, fiber, potassium, magnesium intake; body fat mass; and sistolic blood pressure. However, there weren’t diffference in energy, carbohydrate, protein, sodium, calcium intake, and diastolic blood pressure between vegetarian group and nonvegetarian group